Impatiens hirsutisepala (Balsaminaceae), a new record for the flora of Vietnam - Anh Le, Tuan; Sankaran Hareesh, Vadakkoot; Hong Truong, Luu; Dat Nguyen, Quoc; Huu Cuong, Nguyen; Chinh, Vu Tien (Academia Journal of Biology, 2025)
Species of Impatiens hirsutisepala new distribution central Vietnam, the new record species shows similarities with I. hirsutisepala shows similarities with Impatiens marianae in its creeping densely pilose stem, petiole, lamina, densely pubescent inflorescence axis, lateral sepals, lower sepal, curved spur, dorsal petal (cucullate) and ovary, but differs from the latter in having orange-red flowers, pale reddish orbicular lateral sepals, navicular lower sepal with abruptly constricted spur and dorsal petal with blunt horn. A detailed description along with colour photographs, and similarities with allied species are illustrated in detail are provided.